Preservasi Pengetahuan Budaya Dan Kearifan Lokal Sebagai Program Berkelanjutan Di Perpustakaan Kampung Budaya Polowijen - Yuniar, Hefifa Rhesa; Dannie, Surya; Junaidi, Fahmi (Jurnal FPPTI, 2023)
Polowijen Village is one of the villages that has historical heritage in Malang City. The local wisdom and traditional culture maintained today have made the Polowijen sub-district designated as the thematic village by the Mayor of Malang in 2017 with the name Kampung Budaya Polowijen. Its research helps preserve and promote the Polowijen cultural village so that global influences and foreign culture do not erode it. It is necessary to encourage this existing culture in various media, guide residents, and conduct audio-visual documentation, which can later be utilized for the next generation. This writing uses a descriptive method that describes the implementation of the best practice concept that has been carried out to save and preserve the cultural and indigenous knowledge in the Kampung Budaya Polowijen. The results of this writing activity are in the form of documentation relating to cultural activities and local wisdom in the Kampung Budaya Polowijen. The preservation activities' output was quite diverse: first, an online knowledge directory; second, a collection of cultural objects on Android application-based; third, repackaging the video documentation in a CD Drive and a pocketbook.